Tourism and diversity - Zsuzsanna Bacsi (DETUROPE)
Cultural attractions are often linked to unique features of the host population, and are often related to a national minority or a segment of the population that preserved their traditions. Ethnically or religiously varied countries may often have such unique attractions, that seem exotic and appealing to tourists. Multiculturality is often an attraction for tourism, offering generally an authentic experience for visitors of different backgrounds. Besides, an ethnically or linguistically varied population can also provide a linguisticaly more skilful labour force, that is more sensitive to the needs of visitors coming from different cultures, and thus create a more comfortable environment for them. The issue of multicultural societies has recently become a sensitive issue, due to global mass migration. There is a belief that ethnic or cultural fractionalisation would necessarily bring about difficulties of understanding and cooperation, leading to lower economic performance, less stable economic and social processes and, ultimately a slowdown of economic output. The resulting conflicts, difficulties may frighten away tourists and lead to the vulnerability of the tourism sector in very heterogeneous countries. On the other hand, ethnic fractionalisation and the resulting cultural diversity can be welcome as valuable resources as the varied pool of knowledge, traditions, skills, customs, that can enhance innovative ideas and creativity. In the present paper evidence is looked for the relationship between ethnic, linguistic and religious diversity and tourism performance in a cross-country statistical analysis of 155 countries of the world. Statistical analysis of 155 countries show, that although there is a tendency of lower tourism performance with greated fractionalisation of the society, the most popular and successful tourism destinations are often multicultural and multiethnic societies.